Evaluation of the Medicinal Properties of the “Gulkhairi” Plant Used in the Treatment of Respiratory Tract Diseases By Its Chemical Composition - Asqarov Ibrohim Rahmonovich; Otakhonov Qobuljon Qaxramonovich; Xojiqulov Azizbek Sobirovich; G‘offorov Islombek Raximjon og‘li (Scientific Trends, 2023)
The article provides information on the importance of vitamins used in the treatment of respiratory diseases, the determination of the amount of water-soluble vitamins in the extract of Althea root and vegetative organs in a 0,1 N hydrochloric acid solution using the "High-Performance Liquid Chromatography" method.
Keywords: drug treatment for respiratory diseases, water-soluble vitamins, Altea root, Altea autonomic organs, ointments, compresses, nutritional supplements and creams, traditional and scientific medicine.